A group decision support system for selecting complex objects in a web environment. (2nd February 2009) - Petrovsky, Alexey B.; Afanasjev, Viktor M.
This paper considers the problem of selecting objects with a modular structure (e.g. equipment, CAD/CAM/CAE systems, training programmes, and so on) as a problem of group decision-making. Each object configuration is described by many quantitative and/or qualitative attributes and may exist in several copies, which could be estimated by several persons under multiple criteria. A new selection approach combines multiple-criteria decision support methods based on the verbal decision analysis and the theory of multiset metric spaces. We present the main steps of an algorithm and discuss a general framework for a Web-based Group Decision Support System (Web-GDSS) for the selection of complex objects with a modular structure. Examples of possible Web-GDSS applications are considered.